DNA damage in dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) from European seas - Hylland, Ketil; Skei, Bjørn Borge; Brunborg, Gunnar; Lang, Thomas; Gubbins, Matthew; Le Goff, Jérémie; Burgeot, Thierry (Marine Environmental Research, 2017)
International audience Dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) were collected from coastal and offshore locations in the Baltic (dab only), North Sea (haddock from one location only) and Iceland. Blood was analysed for DNA strand breaks using the comet assay and liver samples for DNA adduct concentrations. DNA strand breaks were at background levels in dab from the two Iceland locations and from the Dogger Bank. The highest levels were observed in dab from the Firth of Forth, Ekofisk and the German Bight. Hepatic DNA adducts in dab were highest at Ekofisk, in the Baltic and Dogger Bank, below detection limit in dab from Iceland and low in dab from the Firth of Forth and German Bight. There was large variation in DNA strand breaks between locations and individuals for haddock, particularly from Iceland. Adduct concentrations were elevated in haddock from both Iceland and the Firth of Forth. A general linear model (GLM) suggested that, in addition to location, the size of dab and its general condition contributed to explaining the observed variability in DNA strand breaks. A GLM for adducts in dab similarly allocated most of the variability to location, but with a possible contribution from CYP1A activity. There were no apparent differences between male and female dab for any of the methods. There was no obvious relationship between strand breaks and adducts in the same fish although dab from Ekofisk and Iceland had respectively high and low responses using both methods. The results from this large-scale study showed pollution-related genotoxicity for dab, that fish blood samples can be conserved prior to comet analyses and that there are clear species differences in genotoxic responses even when collected at the same location.